Amorphous manganese polyphosphates: preparation, characterization and incorporation of azo dyes - de Oliveira, Luiz Fernando C.; Silva, Mauricio A. P.; Brandao, Adilson R.; Stephani, Rodrigo; de Oliveira, Carlos Ivan R.; Goncalves, Rogeria R.; Barbosa, Anne J. [UNESP]; Barud, Hernane S. [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Springer, 2009)
Amorphous Mn(2+) polyphosphate materials were prepared at room temperature through the coacervation of polyphosphate solutions. These new materials display the typical Mn(2+) red emission with a broad band centered at 15,290 cm(-1) (bandwidth-1,320 cm(-1)). Excitation spectra display typical Mn(2+) (d(5)) absorption bands assigned to transitions from the (6)A(1g) ground state to the (4)T(2g), ((4)A(1g), (4)E(g)), (4)T(2g), and (4)T(1g) Mn(2+) excited states. Transition energies allow estimating the Mn(2+) ligand field strength as intermediate between the one observed in Mn(2+) aqueous solutions and the one observed in Mn(2+) phosphate glasses. Azo dyes, methyl red and methyl orange, were incorporated into the manganese polyphosphate coacervates structure. Raman scattering and visible light reflectance results show azo dyes acid forms inside the hydrated polyphosphate structure and sensitivity to the atmosphere pH. Release of azo dyes species was observed from these new solid hybrid materials in aqueous medium.
Keywords: Manganese polyphosphate coacervate; Methyl orange; Methyl red; Raman; Mn luminescence